Future Bachelors Self-Organization as a Pedagogical Problem - Balachenkov D. A., Diorina N. V. (Pedagogy, Psychology, Society, 2021)
the quality of bachelors’ professional training depends on many factors; however, nowadays the ability of students to self-organization is one of the most important, since self-organization is aimed at creating conditions for the effective use of their capabilities. This article offers a variety of interpretations and views on the concept of «self-organization» in pedagogical science.
Keywords: учебно-профессиональная деятельность; самоорганизация; бакалавры; self-organization; конкурентоспособность выпускников вуза; bachelors; competitiveness of university graduates; educational and professional activities